ANALISIS PENERAPAN MARKETING MIX TERHADAP PENJUALAN (Studi Kasus Pada Ruwat Coffee Boyolali) - Zalukhu, Yufinus; Hegy Suryana, Alean Kistiani; Rahayu, Listyowati Puji (EKOBIS, 2025)
Wash reason for this study was to decide the impact of the advertising blend, to be specific item, value, spot, and advancement deals on sales at Ruwat Coffee Boyolali, and to find out which one is the most dominantBaT. the impact between item, value, advancement, and area on client deals at Ruwat Espresso in Boyolali. The populace in this study were all clients at Ruwat Espresso Boyolali and the quantity of tests in the review were 100 guest respondents.In view of the consequences of the t test, it was gotten that the item factor didn't essentially affect deals, the cost variable fundamentally affected deals, the area variable didn't altogether affect deals, the advancement variable impacted deals.While the F test along with item, value, area, and advancement essentially affect deals. The aftereffects of the investigation of the coefficient of assurance (????2) obtained Adjusted Rsquare (R2) of 0.829. Means that variations in changes in sales variables can be explained by product, price, location, and promotion of 82.9%. While the remaining 17.1% is explained by other variables outside the model, from the results of the analysis it is known that the most dominant factor influencing consumer satisfaction is promotion, this is because promotion has a t-count value of 0.001 compared to other variables, namely price of 0.005 , location of 0.126, promotion of 0.055.This proves the hypothesis which states "allegedly the most dominant promotion to sales at Ruwat Coffee Boyolali is proven to be true, because the most dominant is promotion.